Everything you need to know about dealing with sexual assault - Kaminker, Laura (New York : Rosen Pub. Group, 2000)
Discusses the myths and facts surrounding sexual assault and rape, the physical and psychological consequences, suggests ways to stay safe, and explains what to do if sexually assaulted.
Includes bibliographical references (p.62) and index.
Accelerated Reader AR
Keywords: Rape -- United States -- Juvenile literature; Acquaintance rape -- United States -- Juvenile literature; Young women -- Crimes against -- United States -- Juvenile literature; Rape; Acquaintance rape; Young women -- Crimes against; Dating violence